SCC and Corrosion Fatigue characterization of a Ti-6Al-4V alloy in a corrosive environment – experiments and numerical models (Fracture and Structural Integrity, 2014)
In the present article, a review of the complete characterization in different aggressive media of a Ti-6Al-4V titanium alloy, performed by the Structural Mechanics Laboratory of the University of Bergamo, is presented. The light alloy has been investigated in terms of corrosion fatigue, by axial fatigue testing (R = 0.1) of smooth and notched flat dogbone specimens in laboratory air, 3.5% wt. NaCl–water mixture and methanol–water mixture at different concentrations. The first corrosive medium reproduced a marine environment, while the latter was used as a reference aggressive environment. Results showed that a certain corrosion fatigue resistance is found in a salt water medium, while the methanol environment caused a significant drop – from 23% to 55% in terms of limiting stress reduction – of the fatigue resistance of the Ti-6Al-4V alloy, even for a solution containing 5% of methanol. A Stress Corrosion Cracking (SCC) experimental campaign at different methanol concentrations has been conducted over slightly notched dog-bone specimens (Kt = 1.18), to characterize the corrosion resistance of the alloy under quasi-static load conditions. Finally, crack propagation models have been implemented to predict the crack propagation rates for smooth specimens, by using Paris, Walker and Kato-Deng-Inoue-Takatsu propagation formulae. The different outcomes from the forecasting numerical models were compared with experimental results, proposing modeling procedures for the numerical simulation of fatigue behavior of a Ti-6Al-4V alloy.
Keywords: Corrosion Fatigue